2015
DOI: 10.1111/cbdd.12543
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Oxygen‐containing Heterocyclic Ring‐fused 23‐Hydroxybetulinic Acid Derivatives as Antitumor Agents

Abstract: A collection of isoxazole and oxadiazole substituted 23-hydroxybetulinic acid (HBA) derivatives were designed, synthesized and evaluated for their antitumor activity. Most of the newly synthesized compounds exhibited more potent antiproliferative activity than patent compound 23-hydroxybetulinic acid, especially 13e and 14a were about four- to sevenfold more potent against all tested cancer cell lines than 23-hydroxybetulinic acid. Furthermore, the in vivo antitumor activity of 13e and 14a was validated in H22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Thus, exploring the mechanisms of ROS production and the relationship between mitochondrial dysfunction and ROS production would provide an in-depth understanding of the antitumour mechanisms of BA, 23-HBA and their derivatives. Recently, several in vivo antitumour experiments assessing 23-HBA derivatives against H22 liver cancer and B16 melanoma have been reported [25, 3133], but these derivatives showed weak antitumour activity. Therefore, the development of novel 23-HBA derivatives with excellent in vivo antitumour activity is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exploring the mechanisms of ROS production and the relationship between mitochondrial dysfunction and ROS production would provide an in-depth understanding of the antitumour mechanisms of BA, 23-HBA and their derivatives. Recently, several in vivo antitumour experiments assessing 23-HBA derivatives against H22 liver cancer and B16 melanoma have been reported [25, 3133], but these derivatives showed weak antitumour activity. Therefore, the development of novel 23-HBA derivatives with excellent in vivo antitumour activity is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, Zhang and co-workers have been using similar approaches, to the previously described, to synthesize heterocycle-fused HBA derivatives, starting from the protected form of 3-oxo-HBA 123 (Scheme 32) [80,81,82]. They prepared pyrazine-, pyrazole-, and isoxazole-fused HBA derivatives 135 – 137 , which were assessed for their antitumor activity against cancer cell lines.…”
Section: Synthesis Of Heterocycle-fused Ba/hba Derivativesmentioning
confidence: 99%
“…Moreover, compound 136e (IC 50 = 5.58 and 6.13 µM against B16 and SF763 cancer cell lines, respectively) displayed the most potent activity among the pyrazole-fused HBA series [81]. In addition, compounds 137a and 137e (IC 50 = 6.08–10.04 µM and 6.94–9.74 µM, respectively, against cell lines HL-60, BEL-7402, SF-763, Hela, and B16) were the most potent derivatives among the isoxazole-fused HBA series [82]. Regarding the synthesis of these heterocycle-fused HBA derivatives, the pyrazine-fused HBA derivative 132 was obtained in 68% yield through the reaction of 123 with ethylenediamine and sulfur in refluxing morpholine.…”
Section: Synthesis Of Heterocycle-fused Ba/hba Derivativesmentioning
confidence: 99%
“…Anemoside A3 also showed substantial content in the herb and exerted cognitive enhancing, neuroprotective and vasorelaxing effects (Gao et al, ; Ip et al, ; Zhang et al, ). Moreover, 23‐hydroxybetulinic acid, the aglycone of anemoside B4 and anemoside A3, exhibited anti‐inflammatory and strong cytotoxicity in several cancer cell lines, such as human leukemia HL‐60 cells, hepatocellular carcinoma, cervical adenocarcinoma and melanoma cells (Liu et al, ; Suh et al, ; Zhang et al, ). It was demonstrated that 23‐hydroxybetulinic acid induced apoptosis in HL‐60 cells via the downregulation of pro‐apoptotic gene bcl‐2 expression and telomerase activity as well as the upregulation of the apoptotic gene beclin‐1 expression (Ye & Ji, ).…”
Section: Introductionmentioning
confidence: 99%